Why Government Policies Can’t Be Optimization in Providing Housing for Low-Income Communities? - Wijaya, Mendra; Zanariah, Zanariah; Gafar, Tengku Fahrul (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
The government in Indonesia makes various policies to handle the issue of low income communicties (MBR) housing and reduce backlog. The implementation of housing and residential area plicies should yield better results. The authority of MBR housing affairs is also not distributed to local government, and there are overlapping policies between Law Number 23 of 2014 about regional government and Law Number 1 of 2011 about housing and residential areas. This study implements a qualitative method by using a descriptive approach that analyzes data and documents from central government agencies that carry out governement affairs concerning housing and residential areas in Indonesia and other related agencies. The results of the study show that central government cannot stand alone in housing development for low-income communities because the distribution of authority to local governments is not good. The government needs contributions from the private sector. Suppose development is handed over to the housing and residential private sectors. The contruction of housing in MBR, which has become the state’s responsibility to meet its citizens’ basic needs, will change to a business orientation, even though the government is encouraging to provide various subsidies and financing mechanisms. One of the programs from the government is FLPP, which stands for Housing Finance Liquidity Facility. The program encourages housing finance to support low-income communities. Then, proceed with the specific housing program called the One Million Houses Program, which can reduce the backlog in residential construction. The program will proceed with the Public-Private Partnership (PPP) model, which ultimately involves the private sector in developing MBR. The implication of this study is that the implementation of government affairs concerning housing and settlement areas, especially the development of housing for MBR, is fundamentally a mandatory basic service affair, a concept inconsistent with its implementation.